The Project-Based Learning Practices in the Teaching of Writing Course - Fatmawati, Ayu; Musthafa, Bachrudin; Gunawan, Wawan (Lingua Cultura, 2023)
The qualitative research aimed to observe Project-Based Learning (PjBL) implementation in writing courses viewed from the project types and the teaching-learning activities. Several activities in project-based learning implementation could be modified to meet various students’ needs, unexceptionally in the same subject. The various patterns of PjBL often resulted in the bias of its implementation among teachers who wanted to conduct this teaching model. The participants were the lecturers who taught the Professional Writing course in the fourth semester. Data were collected using observation of classroom activities, semi-structured interviews, and documentation. The collected data were analyzed using thematic analysis, emphasizing identifying, analyzing, and interpreting patterns of meaning within qualitative data. The findings show that the project types are different in the form of the final output: business plans and video essays. The other findings find that there is a variety of teaching-learning activities, but they have identical project-based learning patterns, namely (a) preparation, (b) planning, (c) creating a project, (d) monitoring and revising, and (e) evaluation. PjBL provides some advantages for students. Thus, it is suggested that all EFL (English as a Foreign Language) lecturers implement those five project-based learning patterns in their classes.